Pengaruh durasi fermentasi terhadap karakteristik selulosa bakterial dan rendemen dalam produksi nata de soya: Effect of fermentation duration on bacterial cellulose characteristics and yield in nata de soya production - Isnaeni, Nur; Eryna, Rury (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Cellulose is widely used in industries such as paper, textiles, and pharmaceuticals. A method to obtain pure cellulose is nata de soya production using Acetobacter xylinum, which converts glucose into cellulose through fermentation. Tofu wastewater serves as a suitable medium due to its rich organic content. Besides cellulose production, this process also helps reduce environmental pollution. This study aims to determine the effect of fermentation duration on biomass, yield, and microscopic characteristics of bacterial cellulose nata de soya. Fermentation process was carried out with time variations of 6, 12, 18, 24 and 30 days with three replicates each. The nata de soya product then measured for wet weight, washed, and pressed to reduce the moisture content before dried at 50°C until get a constant weight. Cellulose characterization was carried out using a dino-Lite microscope and a Scanning Electron Microscope (SEM) instrument to observe the structure of bacterial cellulose fibres. The results showed that the duration of medium fermentation affected the thickness of nata de soya and the amount of cellulose yield. Based on the nata biomass, the best fermentation duration is 24 days, which demonstrate the highest average wet weight of 494 grams/L medium. However, for the dry weight and the percentage of yield, the best result was obtained at the fermentation duration on the 30th day, which was 26.23 grams/L medium; 5,28%, respectively. It is concluded as the longer fermentation duration, the more fibre tendrils and bacterial cellulose content the nata de soya is produced.